1993
DOI: 10.1128/iai.61.8.3466-3475.1993
|View full text |Cite
|
Sign up to set email alerts
|

Newborn piglet model for campylobacteriosis

Abstract: An in vivo model system for human campylobacteriosis has been developed in which colostrum-deprived newborn piglets are orally challenged with an invasive strain of Campylobacterjejuni. Piglets developed clinical symptoms and histopathological lesions similar to those observed in humans infected with C. jejuni. Gross lesion examination at autopsy revealed the presence of edema, hyperemia, and mucus. Histopathologic examinations by light and transmission electron microscopy demonstrated damage to surface epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 29 publications
4
41
0
1
Order By: Relevance
“…Both in vivo and in vitro studies have demonstrated that C. jejuni both adheres to and invades the cells of the intestinal epithelium (Newell and Pearson, 1984;De Melo et al ., 1989;Konkel and Joens, 1989;Wassenaar et al ., 1991;Babakhani et al ., 1993;Oelschlaeger et al ., 1993). Mutants defective in their ability to be internalized into cultured epithelial cells have reduced virulence in animal models (Yao et al ., 1997) suggesting that bacterial internalization is important in campylobacter pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and in vitro studies have demonstrated that C. jejuni both adheres to and invades the cells of the intestinal epithelium (Newell and Pearson, 1984;De Melo et al ., 1989;Konkel and Joens, 1989;Wassenaar et al ., 1991;Babakhani et al ., 1993;Oelschlaeger et al ., 1993). Mutants defective in their ability to be internalized into cultured epithelial cells have reduced virulence in animal models (Yao et al ., 1997) suggesting that bacterial internalization is important in campylobacter pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intracellular organisms have been observed by electron microscopic examination of C. jejuni-infected individuals with colitis (Van Spreeuwel et al, 1985). Intracellular bacteria have also been observed in infected infant macaque monkeys (Russell et al, 1993) and newborn piglets (Babakhani et al, 1993). Both animal models closely mimic human C. jejuni infections with the development of self-limiting diarrhoeal disease with acute colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Several animal models, such as Galleria mellonella larvae [102], colostrum-deprived piglets [103], gnotobiotic piglet [104], naïve swines [105], and ferrets [106] were successfully used for the study of numerous aspects of C. jejuni pathogenesis. However, each animal model showed strong limitations in terms of employing or comparing with human conditions upon C. jejuni infection [54].…”
Section: Generation Of Secondary Abiotic Mice To Overcome Colonizatiomentioning
confidence: 99%